From Femininity to Resistance: Re-signifying Pink in the 17+8 People’s Movement in Indonesia - Wahyu Mahesa Miarta; Muhammad Abduh; Raesita Rakhmawati Rosadi; Jauhar Wahyuni; Rizqi Mutqiyyah; Muhammad Danu Winata; Muhammad Zawil Kiram (Journal of Southern Sociological Studies, 2026)
This article examines how pink is re-signified from a gender-coded color associated with softness and femininity into a symbol of solidarity, civic courage, and nonviolent resistance within Indonesia’s 17+8 People’s Movement. It asks how street practices and digital circulation reshape the meaning of pink, support collective identity, and connect gendered symbolism to demands for economic justice and governmental accountability. The study combines semi-structured interviews with three participants—a field activist, a digital poster artist, and a homemaker—participant observation, and analysis of protest clothing, placards, profile frames, social media images, and movement narratives. Drawing on Barthesian semiotics, feminist visual analysis, and Southern sociology, the findings show that pink operates as a care-based counter-sign that converts associations of care, domesticity, and femininity into public courage. It also functions as a vernacular semiotic infrastructure linking embodied protest, household economic pressures, religious respectability, youth creativity, and networked media. Pink lowers the threshold of recognition and participation and translates concerns about prices, labor, inequality, and state legitimacy into a culturally legible form. Its rapid circulation, however, creates risks of aestheticization, decontextualization, and commercial co-optation, making continual anchorage to the 17+8 demands essential. By theorizing from the Indonesian case, the article treats Global South actors as producers of concepts and contributes to visual social movement studies, feminist sociology, digital activism, and Southern sociological perspectives.